Improved cutaneous melanoma survival stratification through integration of 31-gene expression profile testing with the American Joint Committee on Cancer 8th Edition Staging. Issue 2 (2nd February 2022) - Wisco, Oliver J.; Marson, Justin W.; Litchman, Graham H.; Brownstone, Nicholas; Covington, Kyle R.; Martin, Brian J.; Quick, Ann P.; Siegel, Jennifer J.; Caruso, Hillary G.; Cook, Robert W.; Winkelmann, Richard R.; Rigel, Darrell S.
Abstract : Supplemental Digital Content is available in the text. Abstract : Cutaneous melanoma (CM) survival is assessed using averaged data from the American Joint Committee on Cancer 8th edition (AJCC8). However, subsets of AJCC8 stages I–III have better or worse survival than the predicted average value. The objective of this study was to determine if the 31-gene expression profile (31-GEP) test for CM can further risk-stratify melanoma-specific mortality within each AJCC8 stage. This retrospective multicenter study of 901 archival CM samples obtained from patients with stages I–III CM assessed 31-GEP test predictions of 5-year melanoma-specific survival (MSS) using Kaplan–Meier and Cox proportional hazards. In stage I–III CM population, patients with a Class 2B result had a lower 5-year MSS (77.8%) than patients with a Class 1A result (98.7%) and log-rank testing demonstrated significant stratification of MSS [ χ 2 (2df, n = 901) = 99.7, P < 0.001). Within each stage, 31-GEP data provided additional risk stratification, including in stage I [ χ 2 (2df, n = 415) = 11.3, P = 0.004]. Cox regression multivariable analysis showed that the 31-GEP test was a significant predictor of melanoma-specific mortality (MSM) in patients with stage I–III CM [hazard ratio: 6.44 (95% confidence interval: 2.61–15.85), P < 0.001]. This retrospective study focuses on Class 1A versus Class 2B results. Intermediate results (Class 1B/2A) comprised 21.6% of cases with survival rates between Class 1A and 2B, and similar to 5-year MSS AJCC stage values. Data from the 31-GEP test significantly differentiates MSM into lower (Class 1A) and higher risk (Class 2B) groups within each AJCC8 stage. Incorporating 31-GEP results into AJCC8 survival calculations has the potential to more precisely assess survival and enhance management guidance.